2013
DOI: 10.1021/nn404544e
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes for the Label-Free Detection of Biomarkers

Abstract: Carbon nanotubes (CNTs) have been of high interest because of their potential to complement or to replace current biomedical sensor and assay techniques. By taking advantage of their unique electrical and optical properties, CNTs can be integrated into highly sensitive sensors and probes. We highlight recent advances toward applying CNTs to the biomedical field, focusing on a report by Reuel et al. in this issue of ACS Nano, wherein the inherent near-infrared (NIR) fluorescence of functionalized arrays of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…[76,77] Recent reviews can be found on CNTs in biotechnology and drug delivery, [69,[78][79][80] electronics, [81] energy production and storage, [82][83][84] and catalysis. [88] CNTs have been used to sense biological molecules [89][90][91][92][93][94][95] and vapors of industrial gases and explosives. [88] CNTs have been used to sense biological molecules [89][90][91][92][93][94][95] and vapors of industrial gases and explosives.…”
Section: Metal Chalcogenide or Pnictide Nwsmentioning
confidence: 99%
“…[76,77] Recent reviews can be found on CNTs in biotechnology and drug delivery, [69,[78][79][80] electronics, [81] energy production and storage, [82][83][84] and catalysis. [88] CNTs have been used to sense biological molecules [89][90][91][92][93][94][95] and vapors of industrial gases and explosives. [88] CNTs have been used to sense biological molecules [89][90][91][92][93][94][95] and vapors of industrial gases and explosives.…”
Section: Metal Chalcogenide or Pnictide Nwsmentioning
confidence: 99%
“…The great sensitivity of the electron network in CNTs and graphene to surface electrostatics makes them especially favourable, and single-walled CNT field-effect transistors are an attractive platform for proteinbased biosensors [63,64].…”
Section: Progress Towards Functional Devicesmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) are another useful option as carbon nanomaterials for improving the performance of biosensors [27,28,29]. hCG sensors have been constructed by using single-wall CNT-based screen-printed electrodes modified with anti-hCG antibody [30].…”
Section: Immunosensors For Glycoproteinsmentioning
confidence: 99%